TAFSIR INDONESIA PADA ABAD 20 M: TAFSIR RINGKASAN KEMENAG RI DAN KONSEP AYAT KEPEMIMPINAN - M. Hafidzul Umam; Akhmad Dasuki (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study explores the summary interpretation published by the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI) alongside the Qur'anic concept of leadership. Employing a thematic approach, the research gathers Qur'anic verses relevant to the theme of leadership. The findings reveal that the Ministry's summary interpretation offers a broad and structured understanding of diverse Islamic themes, including leadership, through a thematic framework. Leadership in the Qur'an is articulated through three primary roles: Caliph, Imam, and Ulil Amri, each carrying distinct functions and obligations. The principles of leadership outlined in the Qur'an serve as foundational guidance for leaders, encouraging them to fulfill their responsibilities in accordance with Islamic values and teachings